DAMPAK PERTENTANGAN DIAMETRAL DAN STRATEGI PEMERINTAH PADA TAX EVASION - Risnaningsih .; Sheny Tanuwidjaja (REFORMASI, 2013)
Diametric contradiction by Halim means that the tax authorities as the beneficiary in the process of tax revenue, will always strive to achieve the target revenue into the state coffers as much as possible. On the other hand, the community taxpayers, who should be paying taxes without getting any refund due payment services directly it does, will seek to reverse that is looking for ways to reduce the tax payable to be paid to the state treasury. The results of the research that has been done on the Civil Service Office of the District Municipality of Malang said that the positive impact of diametric opposition to tax evasion is 23.1 % of the 65 respondents felt enthusiastic about paying taxes every year, respondents reported the tax in accordance with the facts, and also by looking at the tax realtor cases in Indonesia , the respondent continued to pay taxes each year without being affected by the case. While the negative impacts is that although the respondents already know about taxes but 7.7% of respondents in filling the Annual Tax (SPT) still use the help of others as respondents still having trouble filling the Annual Tax (SPT). Although respondents already know about taxes but the majority of respondents still much that delinquent taxes in the amount of 7.7 % . Strategy by the government so that the individual taxpayer are excited to pay taxes is to increase knowledge about taxes, there should be openness in Government Officers